2022
DOI: 10.1177/08465371221120263
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-Induced Toxicities: An Imaging Primer

Abstract: The Coronavirus Disease of 2019 (COVID-19) pandemic has caused significant delays in the delivery of cancer treatments in Canada. As cancer treatment and imaging volumes return to normal, radiologists will encounter more cases of chemotherapy-induced toxicities. These toxicities have varied appearances on imaging, and can affect multiple organ systems. The purpose of this review is to offer a unified resource for general radiologists regarding the imaging appearances of chemotherapy-induced toxicities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 76 publications
(134 reference statements)
2
15
0
1
Order By: Relevance
“…[8] Patil et al also showed that ChatGPT-4 answered significantly more accurately than Bard in the radiology examination (87.1% vs 70.4%; P < .001). [9] In a study using a question bank of the American College of Emergency Medicine, ChatGPT-4 showed a superior performance rate than ChatGPT-3.5 (82.1% vs 61.4%), which was almost similar to the human level. [5] These performance rates of ChatGPT-4 and ChatGPT-3.5 are similar to those reported in our study (75.6% and 56.9%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…[8] Patil et al also showed that ChatGPT-4 answered significantly more accurately than Bard in the radiology examination (87.1% vs 70.4%; P < .001). [9] In a study using a question bank of the American College of Emergency Medicine, ChatGPT-4 showed a superior performance rate than ChatGPT-3.5 (82.1% vs 61.4%), which was almost similar to the human level. [5] These performance rates of ChatGPT-4 and ChatGPT-3.5 are similar to those reported in our study (75.6% and 56.9%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to past studies, our analysis also found that ChatGPT outperformed Bard, but responded slower. [13][14][15][16] Although slower, the difference between chatbots may not be significant during everyday use. An important deficiency in both AI chatbots' responses is that they did not communicate the probability of various adverse events, and it is uncertain how well they would do so if asked explicitly.…”
Section: Discussionmentioning
confidence: 99%
“…Oncologic emergencies can result from local effects of the primary tumour, its metastases, paraneoplastic syndromes, or reaction to the chemotherapeutic agents. [1][2][3][4][5][6][7][8][9][10][11] Many oncological emergencies are signs of advanced, stage IV disease, but occasionally patients present to the emergency department (ED) with a previously unknown primary tumour responsible for acute clinical symptoms. Imaging plays a crucial role in both the initial diagnosis and therapeutic decision process.…”
Section: Introductionmentioning
confidence: 99%